(untitled) (Journal of the Bangladesh Agricultural University, 2020)
A field experiment was conducted at the Crop Botany Field Laboratory of Bangladesh Agricultural University, Mymensingh to study the effect of varieties and different doses of nitrogen on growth and yield parameters of sorghum. It was a two factorial experiment. Factor one consisted of three levels of nitrogen viz. 69, 92, 115 kg N ha-1 and factor two consisted of four varieties of sorghum viz. BD700, BD707, BD722 and Hybrid Sorgo. The experiment was laid out following Randomized Complete Block Design (RCBD) with three replications. Result revealed that both variety and application of nitrogen doses had significant effect on all of the morphological and physiological characters (plant height, total number of leaves per plant, leaf length, leaf width, stem diameter, fresh and dry weight of shoot and root, relative greenness (SPAD value), Fv/Fm value); yield contributing characters (panicle length, branches per panicle, grain yield) at harvesting stage and proximate composition of grain and leaf (crude protein, crude fiber, ether extract, nitrogen free extract and total ash). The tallest plant, maximum fresh and dry weight of shoot, less crude fiber were recorded from BD722 when treated with 69 kg N ha-1. The longest panicles, highest number of branches per panicle, maximum grain yield were produced from the same variety (BD 722) with 92 kg N ha-1. The maximum SPAD value, nitrogen free extract and ash in leaf were found in the same variety (BD722) with 115 kg N ha-1. The maximum crude protein and ether extract in leaf was recorded in Hybrid Sorgo with treatment combination 90 and 92 kg N ha-1, respectively. The minimum plant height, fresh and dry weight of shoot, length of internodes, relative greenness of leaf, panicle length, grain yield, crude protein and ash was found in BD707. Among the varieties tested, BD722 was the best in terms of growth characters with 69 kg N ha-1 and in terms of physiological, yield and yield contributing characters with 92 kg N ha-1. Both BD722 and Hybrid Sorgo showed the best performance in chemical composition with different N treatments. On the other hand, BD707 showed inferior performance in all plant characters. J Bangladesh Agril Univ 18(2): 373–378, 2020 https://doi.org/10.5455/JBAU.73998